Strategi Komunikasi Humas Protokol Sumatera Selatan Dalam Menjaga Citra Pemerintah Daerah - Nurmala Sari Yahya; M. Ramadhani Setiawan; Muhammad Yudha Prayoga; Abdur Razzaq; Muhamad Yudistira Nugraha (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to examine the communication strategy of the South Sumatra protocol public relations in maintaining the image of the local government. In the process of achieving this, the focus is on the public relations of the Palembang City Government and several communities living in the city of Palembang. Public relations plays an important role in every institution because public relations plays a role in shaping the image of the company/institution. In shaping the image of an institution, public relations usually has extensive relations. This study aims to determine how the communication strategy of public relations protocol and its obstacles in improving the image of the local government. This type of research uses a qualitative approach. The results of this study indicate that the communication strategy carried out by the Public Relations protocol of the Palembang City Government is to build good communication with the public such as holding personal approaches, press conferences, press conferences, media gatherings. So all of that is solely to build good communication between the government and the media. So that ultimately will improve the image of the Palembang City Government. The obstacles faced by the Palembang City Government public relations are the delay in public relations receiving and disseminating correct information about government activities and policies to the public so that there are media that spread wrong news about the government. If this wrong news is not immediately corrected by the public relations, it will have an impact on the decline in the image of the Palembang City Government. To achieve the Palembang City Government's Public Relations goal of shaping the government's image, hard work, high discipline, and professional expertise in Public Relations are required.